ETHER - a partially forgotten anesthetic - Pożarowska, Kinga; Rosińska, Agata; Orczykowski, Maciej; Tyszkiewicz, Marcin; Choina, Magdalena (Journal of Education, Health and Sport, 2022)
INTRODUCTION: Ether is the common name for diethylether (CH3-CH2-O-CH2-CH3). It is a colorless, volatile and highly flammable liquid with a characteristic pungent odor. It was widely used as an anesthetic in the past and is now a component of solvents. PURPOSE OF THE WORK: The purpose of this paper is to introduce ether as a potentially forgotten substance in the world of Western medicine. Its history, current use, potential for abuse for narcotic purposes, addiction, and the benefits of anesthesia with this agent in impoverished countries. DESCRIPTION OF THE STATE OF KNOWLEDGE: Ether was first synthesized in 1540 by Valerius Cordus. Ether is characterized by rapid absorption, rapid distribution in the central nervous system and rapid, short-lasting effects. Ether has high solubility in blood/gas, which slows both induction and recovery of anesthesia. In developing countries, it is suggested that ether be used as an intraoperative analgesia. But it should be remembered, despite the new psychoactive substances, other inexpensive and readily available intoxicants can be found, among them ether. It has been noted in numerous publications that abuse of ether is associated with abuse of other drugs and/or alcohol dependence. SUMMARY: It is important to remember that ether compounds are widespread. People struggling with the urge to abuse substances can get these substances easily and cheaply. On the other hand, ether anesthesia is a great solution for developing countries. There are situations there that due to lack of funds, some operations are carried out without anesthesia. Ether is cheap, and administering anesthesia with it is quite simple, and could give wonderful relief to these patients.